Treatment Of Post-Operative Chylothorax: The Role Of Intranodal Lymphangiography And Thoracic Duct Disruption - Torres, Tiago Paulino (2024)
Thoracic duct embolization has been increasingly adopted as a first-line therapy of chylothorax and this procedure includes lipiodol lymphangiography, thoracic duct access and embolization. Lymphangiography itself has a therapeutic role, with volume-dependent success rates of 37%-97% and even a reported 100% success rate in outputs of < 500 mL/day. We present a clinical case of a 48-years-old man diagnosed with esophageal squamous cell carcinoma, who underwent esophagectomy and presented with post-operative high-output (> 1L/day) chylothorax; thoracic duct embolization was proposed. Even though thoracic duct access and embolization were not achieved due to technical and anatomical factors, lipiodol lymphangiography and possibly thoracic duct maceration (after several punctures/attempts) contributed to the clinical success of the procedure, and this chylothorax with output values superior to those reported in the literature resolved within three days. As such, the therapeutic role of intranodal lymphangiography and thoracic duct disruption should be taken into account.